From youth to elite: a systematic review of physical fitness characteristics that discriminate competitive swimming levels - Naluri Denay; Juanda Putra (IICET (Indonesian Institute for Counseling, Education and Therapy), 2025)
Competitive swimming performance is influenced by interacting anthropometric, neuromuscular, metabolic, and technical characteristics that vary across competitive levels. This systematic review aimed to identify key physical fitness characteristics in competitive swimmers, examine their differences across performance levels, and determine those most consistently associated with superior performance. Following the PRISMA 2020 framework, a systematic search of Scopus was conducted from inception to December 2025. Of 279 records identified, 18 studies met the inclusion criteria and underwent thematic synthesis following methodological quality assessment using Joanna Briggs Institute checklists. Higher-level swimmers consistently demonstrated greater arm span, stature, and lean mass, with the clearest differences observed in youth and junior populations. Muscular strength and lower-body power, particularly measured through countermovement and squat jumps, showed strong and consistent associations with start and sprint performance. Aerobic capacity, maximal swimming velocity, and critical speed increased substantially from junior to senior levels, with critical speed emerging as a strong correlate of junior performance. At elite levels, stroke index, active drag, and start and turn efficiency became increasingly important discriminators. Overall, the findings provide an integrated, competition-level-specific performance profile that may support talent identification, long-term athlete development, and evidence-based training. Standardized longitudinal, multidomain testing that considers stroke- and distance-specific demands is recommended for future research and practice.